An In Situ Quick X‐ray Absorption Spectroscopy Study on Pt3Sn/Graphene Catalyst for Ethanol Oxidation Reaction. Issue 1 (12th November 2020) - Su, Bing‐Jian; Wang, Kuan‐Wen; Tseng, Chung‐Jen; Lu, Kueih‐Tzu; Pao, Chih‐Wen; Lee, Jyh‐Fu; Sheu, Hwo‐Shuenn; Wu, Kuang‐Hsu; Juang, Jenh‐Yih; Chen, Jin‐Ming
Abstract: Direct ethanol fuel cells (DEFCs) promise the use of ethanol as a bio‐renewable and non‐toxic fuel for energy conversion through the ethanol oxidation reaction (EOR). Well dispersed Pt3 Sn and Pt nanoparticles on graphene (denoted Pt3 Sn/G and Pt/G) support electrocatalysts made with alcohol reduction were tested towards EOR. The HRTEM and XRD characterizations provide the morphology and crystal phase of the Pt3 Sn alloy nanoparticles, which has a uniform particle size of 2.8±0.08 nm, as is consistent with a Pt/G catalyst as reference. According to the in‐situ quick X‐ray‐absorption near‐edge structure (QXANES) spectra during an anodic scan of CV for the EOR test to explain clearly the potential‐dependent electronic state of the prepared electrocatalysts, the white‐line intensities of the Pt L3 ‐edge QXANES spectra and their spectral profiles vary appreciably with the electrode voltage. Moreover, Pt3 Sn/G shows a better EOR performance than Pt/G because SnO2 can improve adsorption and dissociation during the oxidation by an appropriate expansion of the lattice parameters in the PtSn alloy. This work provides insight into the reaction mechanism of dissociative adsorption of ethanol on alloyed Pt surface, which has an important role in enhancing the EOR activity for a complete ethanol oxidation. Abstract : Electrocatalysis : The Pt L3 ‐edge white‐line intensity of Pt3 Sn/G catalysts increases with increasing electrode potential during the forward direction of the CV scan, originating from the dissociative adsorption of ethanol (Pt−CH3 CH2 OHads ) on the Pt surface. However, the active sites of the Pt nanoparticles might be blocked by many oxides such as CO (Pt−COads ) on the alloy surface to reduce the white‐line intensity of Pt L3 ‐edge XAS spectra of Pt3 Sn/G catalysts.